2002
DOI: 10.1046/j.1442-2042.2002.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave treatment for Peyronie’s disease using EDAP LT‐02; preliminary results

Abstract: Background : Peyronie's disease is an idiopathic fibrosis of the tunica albuginea of the penis, which often causes erectile dysfunction. No effective therapy except surgery has been available for Peyronie's disease. We investigated the clinical efficacy of extracorporeal shock wave treatment (ESWT) using EDAP LT-02 as an alternative method of treatment for Peyronie's disease. Methods : Five patients aged 35-65 years were treated by ESWT. All patients had undergone unsuccessful medical treatment before ESWT. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…A general subjective improvement was reported by 65% and 52% of the patients in the ESWT and in the control group, respectively. In this study, a complete disappearance of the plaque was found in 10% of the patients, comparable with the 9.1% rate reported by Gianneo et al [19], whereas in a very small group of patients treated with ESWT and previous unsuccessful oral therapy, plaques disappeared in 25% of the cases [24]. Interestingly, plaque disappearance was reported also in patients who did not receive any specific therapy for Peyronie's disease [28].…”
Section: Trial Endpointssupporting
confidence: 81%
See 2 more Smart Citations
“…A general subjective improvement was reported by 65% and 52% of the patients in the ESWT and in the control group, respectively. In this study, a complete disappearance of the plaque was found in 10% of the patients, comparable with the 9.1% rate reported by Gianneo et al [19], whereas in a very small group of patients treated with ESWT and previous unsuccessful oral therapy, plaques disappeared in 25% of the cases [24]. Interestingly, plaque disappearance was reported also in patients who did not receive any specific therapy for Peyronie's disease [28].…”
Section: Trial Endpointssupporting
confidence: 81%
“…Based on the various trial designs developed for ESWT, the absence of a standard protocol regarding patient selection, modalities of shock-wave application, and pre-and post-treatment patient evaluation contributes to making this kind of treatment for Peyronie's disease investigational and not actually fully applicable in everyday clinical practice. 24,25], only patients who had previously failed to respond to oral drug therapy received ESWT, leading to a selection of patients with more severe penile deformities and with a more stable disease. In contrast, a prospective study by Lebret et al [15] was designed to assess the results obtained by ESWT only in patients with recently developed (ie, less than 6 mo) palpable penile plaques.…”
Section: Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that in ≈20% of cases PD improves with no treatment, but in the remainder the disease is static or deteriorates with time. Apart from surgery, no treatment has been shown to definitely help the latter group of patients, except for evidence for some improvement after limited (6 weeks) of SWT [1,11–15]. There was no significant influence of SWT on plaque size [16] but benefits of SWT for pain in men with PD have been reported [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have different opinions on the therapeutic effect of ESWT on PD. The prospective study of Husain et al concluded that ESWT can improve penile curvature and reduce erectile pain; [ 18 ] a small single- arm trial by Kiyota et al proposed ESWT as a surgical alternative in improving or even reversing the formation of fibrous plaques as well as reducing pain, but failed to find an improvement in penile curvature; [ 25 ] Manikandan et al gave relatively optimistic conclusions that ESWT was effective in improving penile curvature and relieving pain during erection, but there was no significant evidence for improvement in erectile function. [ 26 ] Other studies hold a more conservative view.…”
Section: Discussionmentioning
confidence: 99%